Optimized Diagnostic Assays Based on Redox Tagged Bioreceptive Interfaces - Bedatty Fernandes, Flavio C. [UNESP]; Patil, Amol V.; Bueno, Paulo R. [UNESP]; Davis, Jason J. (American Chemical Society (ACS), 2015)
Among the numerous label free electronic biomarker assay methodologies now available, impedance based electrochemical capacitance spectroscopy (ECS), based upon mapping the perturbations in interfacial charging of redox elements incorporated into a biologically receptive interface, has recently been shown to be a convenient and highly sensitive mode of transduction and one which, additionally, requires no predoping of analytical solution. We present, herein, a data acquisition and analysis methodology based on frequency resolved immittance function analysis. Ultimately, this enables both a maximization of assay sensitivity and a reduction in assay acquisition time by an order of magnitude.